Inhaler devices for asthma: do we follow the guidelines?. Issue 3 (1st March 2002) - Child, F; Davies, S; Clayton, S; Fryer, A A; Lenney, W
Abstract : Background: Despite national guidelines for asthma treatment, many children have troublesome symptoms. Aim: To assess the extent to which the use of inappropriate inhaler devices contributes to this problem. Methods: Of 14 813 questionnaires distributed to schoolchildren, 6996 (47%) were returned identifying 1444 children using asthma inhalers. Inhalers were categorised as age appropriate or inappropriate according to national guidelines and were compared with those used by 75 patients attending a hospital clinic. Results: A total of 35% of "schools" and 4% of "clinic" children reported using an inappropriate inhaler device. Most were using metered dose inhalers alone. Twenty four per cent of "schools" children ≤5 years old did not use a spacer. Both children and parents overestimated the child's ability to use their inhaler. Conclusions: Large numbers of children are given inhalers they cannot use. To improve asthma care we must ensure that prescriptions reflect the age and ability of the child. Recent recommendations by the Department of Health in England and Wales stress the importance of seamless care between primary and secondary services. As the management of childhood asthma is guided primarily by secondary care providers, it is therefore imperative that general paediatricians know the difficulties and issues which are occurring in the community. This will enable them to lead and support necessary change.